2006
DOI: 10.1103/physreva.73.033619
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic radio-frequency potentials for the coherent manipulation of matter waves

Abstract: Adiabatic dressed state potentials are created when magnetic sub-states of trapped atoms are coupled by a radio frequency field. We discuss their theoretical foundations and point out fundamental advantages over potentials purely based on static fields. The enhanced flexibility enables one to implement numerous novel configurations, including double wells, Mach-Zehnder and Sagnac interferometers which even allows for internal state-dependent atom manipulation. These can be realized using simple and highly inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
220
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(221 citation statements)
references
References 35 publications
0
220
0
1
Order By: Relevance
“…The coupled states are the magnetic sub-states of an atomic hyperfine ground state and a spatially dependent Zeeman-shift can be used to locally change the coupling strength. Furthermore, the coupling is magnetic and of vector nature, hence not only the amplitudes but also the (local) orientation of the involved RF and static magnetic fields determine the coupling strength [10].…”
Section: Rf Dressed State Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupled states are the magnetic sub-states of an atomic hyperfine ground state and a spatially dependent Zeeman-shift can be used to locally change the coupling strength. Furthermore, the coupling is magnetic and of vector nature, hence not only the amplitudes but also the (local) orientation of the involved RF and static magnetic fields determine the coupling strength [10].…”
Section: Rf Dressed State Potentialsmentioning
confidence: 99%
“…The coupled states are the magnetic sub-states of an atomic hyperfine ground state and a spatially dependent Zeeman-shift can be used to locally change the coupling strength. Furthermore, the coupling is magnetic and of vector nature, hence not only the amplitudes but also the (local) orientation of the involved RF and static magnetic fields determine the coupling strength [10].For our experiments we create the RF dressed state potentials by combining a static Ioffe magnetic trap (B S (r)) with a two component homogeneous RF-field (B RF ) with frequency ω RF and relative phase shift δ.B S (r) = Gxe x − Gye y + B I e z (1) B RF = B A e x cos(ω RF t)+B B e y cos(ω RF t + δ).G is the gradient of the underlying static quadrupol field and B I the magnitude of the Ioffe field. Following [10] the adiabatic RF-potential created can be written as…”
mentioning
confidence: 99%
“…They not only allow us to create standard trapping potentials [12] but can also be used to coherently manipulate matter waves [13,14] or create complicated, nonstandard trapping geometries [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The control parameter λ(t) determines the variation of the confining potential when changing the external parameters [18,19] (for details see below). Through λ(t) it is possible to manipulate the trapped Bose-Einstein condensate, e.g.…”
Section: Model Systemsmentioning
confidence: 99%
“…For instance, v = @( lambda ) ( 0.5 * k * ( grid.x -lambda ) .^2 ); % harmonic confinement potential defines a harmonic confinement potential whose origin is shifted by the control parameter. As another example, we consider the potential of Lesanovsky et al [19] for the transition from a single well to a double well, as shown in Fig. 5.…”
Section: Control Parametermentioning
confidence: 99%